REMAJA DAN PEMAHAMAN AGAMA - Triana Rosalina Noor (Vicratina : Jurnal Ilmiah Keagamaan, 2018)
Abstract. Teenagers are a certain period of human life that has a lot of dynamics. At this period, religious understanding is a guideline for teenagers to protect them from negative effects from environment. This study is a study of literature studies which examines a phenomenon by reference to the supporting theories, in particular theories related to the concept of teenagers and religions. The results of this study indicate that teenager's religiousunderstanding is related to the cognitive development that he goes through. The development of a religious understanding of a teenager is a continuation of the religious understanding that has been gained in the previous development phase of the phases of the children. But the difference is that when the phases of the children's concepts of understanding are real manifested in the real symbolic form, whereas in the youth phase the understanding of religion has been manifested in more abstract form and hypothesis. This means that the concept of a religious understanding of a teen can not be separated from the periode before on their development that has been acquired since childhood. Keywords : Teenagers, Religious Understanding